Effectofkersen (Muntingiacalbura l) Leaf Decoction On Perinal Wound Healing Postpartum Women at Murniati Clinic - Christiani, Meity; Anggraini, Ririn (Cattleya Darmaya Fortuna, 2022)
Childbirth often results in tears in the birth canal, both in the first birth and in subsequent births. A perineal wound is defined as a tear in the birth canal spontaneously or by drying during delivery of the fetus. The impact of a perineal wound on the mother includes infection of the suture wound, and it can spread to the bladder or birth canal so that it can cause complications of bladder infection or infection. birth canal